Neuronal NMDAR Currents of the Hippocampus and Learning Performance in Autoimmune Anti-NMDAR Encephalitis and Involvement of TNF-α and IL-6 - Wang, Xu; Ma, Chi; Liu, Cai-Yun; Li, Guang-Jian; Zhao, Ding; Han, Dong-Feng (Frontiers in Neurology, 2019)
Among autoimmune encephalitis, patients with anti-N-methyl D- aspartate receptor (NMDAR) encephalitis typically present epileptic seizures, memory deficits and psychiatric symptoms. However, the signal mechanisms leading to the functional disorders of autoantibodies are largely unclear. In this study, anti-NMDAR antibody was administered into dentate gyri against the NR1 subunit of the NMDAR. The purpose of the study examined the effects of proinflammatory tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) on neuronal NMDAR currents of the hippocampus in rats with anti-NMDAR encephalitis and we further determined the role played by TNF-α and IL-6 in modulating learning performance. In results, we observed a decrease in amplitude of the NMDAR-mediated excitatory postsynaptic currents (NMDAR-EPSCs) in the hippocampal neurons of animals treated with anti-NMDAR. In those rats with anti-NMDAR, we also observed impaired learning performance in the Morris water maze and spatial working memory test. Of note, cerebral infusion of TNF-α and IL-6 worsened NMDAR-EPSCs and this was accompanied with exaggeration of impaired learning performance. In conclusion, our findings suggest that the role played by neuroinflammation in exacerbating the memory impairment found in animals treated with anti-NMDAR. Anti-inflammation is a potential target in improving the memory impairment induced by anti-NMDA encephalitis.